+0  
 
0
332
3
avatar+18 

6x-3y=9

y=4x-1 

whats the answer?

robswag  Apr 18, 2017
 #1
avatar+80 
+1

the answer is -1...push heart plz :).  You have to use substitution to get the answer...in order to get x you have to replace part of the first formula with the second :)

wgunningham  Apr 18, 2017
 #2
avatar
-1

\(6x-3y=9 \)                   |    \(/3\)

\(2x-y=3\)                   |    \(y=4x-1\)

\(2x-4x+1=3\)

\(-2x+1=3\)                   |   \(-1\)

\(-2x=2\)                   |   \(/-2\)

\(x=-1\)

 

\(y=4x-1\)                   |   \(x=-1\)

\(y=4*(-1)-1\)

\(y=-5\)

 

Should be the right solution. (I hope I made no mistakes)

Guest Apr 18, 2017
edited by Guest  Apr 18, 2017

6 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.